Technopreneurship Engagement: The Behavioral Intentions of Nigerian and Indonesian Undergraduates in an Emerging Society 5.0 - Oladejo, Maruff Akinwale; Wahyuni, Sri; Avrillianda, Decky (Universitas Negeri Semarang, 2022)
Developing the mindset of the younger ones towards technopreneurship engagement is important so as to reduce youth unemployment. This study therefore investigated some factors namely entrepreneurship attitudes, skills, and knowledge (e-ASK) in relation to the behavioral intentions to technopreneurship engagement among Nigerian and Indonesian Undergraduates in an Emerging Society 5.0. The descriptive research design was used. The study was piloted by two null hypotheses. The target population comprised all 5019 undergraduates in two purposively selected Nigerian and Indonesian universities, out of which 336 were selected through stratified random sampling technique. A self-designed, validated, and reliable instrument (r=.88) entitled “Behavioural Intentions of Technopreneurship Engagement Scale (BITES)” was used for data collection. Methods of data analysis were Multiple Regression and Independent t-test. Findings showed that the joint contributions of e-ASK to the variance in technopreneurship engagement were 5.5%. There was also significant difference in behavioral intentions to technopreneurship engagement among Nigerian and Indonesian Undergraduates ((t=-2.376; df=334, p.05). In broad term, this study investigated the behavioral intentions of Nigerian and Indonesian undergraduates towards technopreneurship engagement in an emerging society 5.0. Specifically, the objectives of the study are to: 1) determine the joint contributions of entrepreneurship attitudinal, entre-preneurship skills, entrepreneurship knowledge (e-ASK) in predicting the behavioral intentions for technopreneurship engagement.